1986
DOI: 10.1017/s0022112086001568
|View full text |Cite
|
Sign up to set email alerts
|

Numerical shock propagation using geometrical shock dynamics

Abstract: A simple numerical scheme for the calculation of the motion of shock waves in gases based on Whitham's theory of geometrical shock dynamics is developed. This scheme is used to study the propagation of shock waves along walls and in channels and the self-focusing of initially curved shockfronts. The numerical results are compared with exact and numerical solutions of the geometrical-shock-dynamics equations and with recent experimental investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 8 publications
2
69
0
Order By: Relevance
“…From our knowledge, this is the first time that a comprehensive solution of the GSD Riemann problem is given, together with a link to the p-system. Nevertheless, one can mention the works of Henshaw, Smyth and Schwendeman [15] and Schwendeman [20] where the Whitham GSD equations are rewritten in conservative form. Schwendeman [20] also mentions the fact that the Riemann problem admits simple solutions, but does not give full details.…”
Section: Solutions Of the Riemann Problem In Dimensionmentioning
confidence: 99%
See 1 more Smart Citation
“…From our knowledge, this is the first time that a comprehensive solution of the GSD Riemann problem is given, together with a link to the p-system. Nevertheless, one can mention the works of Henshaw, Smyth and Schwendeman [15] and Schwendeman [20] where the Whitham GSD equations are rewritten in conservative form. Schwendeman [20] also mentions the fact that the Riemann problem admits simple solutions, but does not give full details.…”
Section: Solutions Of the Riemann Problem In Dimensionmentioning
confidence: 99%
“…(i) Lagrangian, or front-tracking, methods have first been experimented [15,18]. In such an approach, the shock front is explicitly discretized by markers evolved in time and regularly resampled.…”
Section: Introductionmentioning
confidence: 99%
“…If the principal interest lies in the shock physics and flow conditions immediately behind the shock, then this reduction of dimensionality is appealing. Geometrical shock dynamics has proved effective for a variety of shock-dynamics problems in multi-dimensional flows including shock focusing in gas dynamics, 9 propagation of shock waves along walls and in channels, 10 shock-wave stability, 7 and shock propagation in non-uniform media. 11 When applied to the symmetrically converging shock of the Guderley type, GSD provides an extremely accurate approximation to power-law exponents and in fact can describe an almost universal shock collapse process from an infinitesimal wave at infinity to a strong-shock state near the point of convergence.…”
Section: Introductionmentioning
confidence: 99%
“…Two numerical approaches have been used for a wide range of problems: the method of characteristics 12,13 and front-tracking methods. 8 Characteristics methods are typically more cumbersome than finite-difference methods and difficult to extend to three dimensional problems, and thus their numerical application has been fairly limited. In front-tracking methods points along the shock front are advanced along rays normal to the front according to the shock Mach number.…”
Section: Methodsmentioning
confidence: 99%
“…Henshaw et al, 8 using a front-tracking method to solve the equations of shock dynamics, analyzed shock focusing and compared calculated results with the experiments of Sturtevant and Kulkarny. 1 They showed that shock dynamics qualitatively reproduces the weak-, moderate-and strongshock behavior illustrated in Fig.…”
Section: Introductionmentioning
confidence: 99%